The Administrative organization and his relation with the academic aspects of the pupils of primary of the Educational Private Centers Magister and José María Arguedas of the district of villa María Del Triunfo 2012 - Rojas Pumacayo, Rita Gladys (2022)
Scientific research we have done is basic, non-experimental causal correlational study factors are twofold: administrative - academic aspect Organization of students from schools and José María Arguedas Magister district of Villa María del Triunfo . The population sample consisted of 10 administrative staff, 40 teachers , 120 students of the two educational institutions. The research design is transactional , correlational , causal . bivariate cross . MANAGEMENT PEI, PAT, PA ORGANIZATIONAL STRUCTURE: Establishment , Organization and Functions Manual for data collection three questionnaires one for executives , one for teachers and one for the student profile structured as a measure and consists of the following were prepared , Administrative Procedures Manual . CURRICULUM (Curriculum Diversification): Areas, Objectives, Content, Strategies, methodological evaluation . Student Profile : Socio- emotional, Cognitive and Psychomotor was applied to the sample . The instruments meet the qualities of validity and reliability. The study raises the following hypothesis: The administrative organization is directly related to the academic aspects (Curriculum - curricular diversification and student profile) students in schools and José María Arguedas Magister district of Villa Maria Triumphal Year 2012. The results allow us to reject the null hypothesis and accept the hypothesis investigated as it has been found according to the Spearman Rho correlation of 0.901 is VERY HIGH and association of variables being highly significant. Furthermore, according to tests of independence (*** p < .000) highly significant, therefore the alternate hypothesis is accepted research says : The administrative organization is directly related to the academic aspects (Curriculum - curricular diversification and student profile) students in schools and José María Arguedas Magister district of Villa María del Triunfo Year 2012.